A BEST PRACTICE OF TWO STAY TWO STRAY IN TEACHING READING - Muhammad Farhan Rafi (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2018)
The purpose of this research is to know the implementation of Two stay Two Stray in teacing reading and students’ responses in teaching reading with the technique of Two Stay Two Stray. The researcher used a descriptive qualitative design in conducting the research. The participant is third semester students of English Department of STKIP PGRI Jombang in academic year 2017/2018. to collect the data the researcher uses a field note, observation checklist and  questionaire. The result shows that Teaching reading by using “Two Stay Two Stray” focused on the students’ center activity and focused on improving students’ skills. Most of the students also agree TSTS influences their ability. It can make them getting easy in understanding the text. In TSTS, the students got many activities in understanding the text. Each activities has special features. The first way concerns to group work and the second way can be group work, pair work, or individual work. Based on the questionnaires given to the students, most of the students enjoy the class well.Keywords: Two Stay Two Stray, Students’ Responses